Investigation of Eph‐ephrin A1 in the regulation of embryo implantation in sows. (26th September 2018) - Fu, Yanfeng; Li, Lan; Fang, Xiaomin; Li, Bixia; Zhao, Weimin; Zhou, Lisheng; Ren, Shouwen
Abstract: Eph A1 and ephrin A1 (Eph‐ephrin A1) is a key receptor–ligand pair of Eph‐ephrin system, which plays important roles in the migration and adhesion of cells, tissue morphogenesis and vasculogenesis in mammals. In order to investigate the regulation of Eph‐ephrin A1 during porcine embryo implantation, the expressions of mRNA and protein of Eph‐ephrin A1 were detected in different reproductive tissues from twelve sows during embryo implantation period on pregnancy day 13, 18 and 24, respectively. Functions of Eph‐ephrin A1 on the migration and adhesion of porcine endometrial epithelial cells were analysed by RNA interference (RNAi), transwell migration assays and MTT assays. Results showed that mRNA levels of Eph‐ephrin A1 were highly expressed in endometrial attachment site when compared to other reproductive tissues ( p < 0.05) and were peaked on pregnancy day 18 during embryo implantation ( p < 0.05). Protein levels of Eph‐ephrin A1 were highly expressed in endometrial attachment site and were peaked on pregnancy day 18 ( p < 0.05). Eph‐ephrin A1 proteins were located in endometrial luminal epithelium, stroma of attachment site and inter‐attachment site during embryo implantation, and the protein levels were higher during implantation compared to pre‐implantation or post‐implantation. Furthermore, silencing ephrin A1 gene significantly reduced the migration and adhesion capacity of porcine endometrial epithelial cells. These findings suggest that the Eph‐ephrin A1 protein likely targets endometrial attachment site to enhance the migration and adhesion of porcine endometrial epithelial cells around pregnancy day 18 during pregnancy in sows.